A season-long examination of team structure and its implications for subgroups in individual sport - Saizew, K.; Evans, M. B.; Allan, V.; Martin, L. J. (Journal of Sport & Exercise Psychology, 2021)
The authors explored how sport structure predisposed a team to subgroup formation and influenced athlete interactions and team functioning. A season-long qualitative case study was undertaken with a nationally ranked Canadian track and field team. Semistructured interviews were conducted with coaches (n = 4) and athletes (n = 11) from different event groups (e.g., sprinters, jumpers) at the beginning and at the end of the season. The results highlighted constraints that directly impacted athlete interactions and predisposed the group to subgroup formation (e.g., sport/event type, facility/schedule limitations, team size/change over time). The constraints led to structural divides that impacted interactions but could be overcome through team building, engaging with leaders, and prioritizing communication. These findings underline how structure imposed by the design of sports impacts teammate interactions and how practitioners, coaches, and athletes can manage groups when facing such constraints. The authors describe theoretical and practical implications while also proposing potential future directions.